Characterization of Two Key Flavonoid 3-O-Glycosyltransferases Involved in the Formation of Flower Color in Rhododendron Delavayi - Sun, Wei; Sun, Shiyu; Xu, Hui; Wang, Yuhan; Chen, Yiran; Xu, Xiaorong; Yi, Yin; Ju, Zhigang (Frontiers in Plant Science, 2022)
Flower color, largely determined by anthocyanin, is one of the most important ornamental values of Rhododendron delavayi. However, scant information of anthocyanin biosynthesis was reported in R. delavayi. We found that anthocyanidin 3-O-glycosides were the predominant anthocyanins detected in R.delavayi flowers accounting for 93.68-96.31% of the total anthocyanins during its development, which indicated the key role of Rd3GTs on flower color formation. Subsequently, based on correlation analysis between anthocyanins accumulation and Rd3GTs expressions during flower development, Rd3GT1 and Rd3GT6 were preliminarily identified as the pivotal 3GT genes for R.delavayi anthocyanin biosynthesis. Then, tissue-specific expressions of Rd3GT1 and Rd3GT6 were examined and their function as 3GT in vivo was confirmed through introducing into Arabidopsis UGT78D2 mutant and tobacco plants. Furthermore, biochemical characterizations showed that both Rd3GT1 and Rd3GT6 could catalyze the addition of UDP-sugar to the 3-OH of anthocyanidin, and preferred UDP-Gal as their sugar donor, cyanidin as the most efficient substrate. This study not only provides insights into the biosynthesis of anthocyanin in R.delavayi, but also makes contribution to understand the mechanisms of its flower color formation.